Body Shaming as a Predictor of Self-Blaming Among Adolescents - Yuliana, Yuliana; Peñaflorida, Greaza; Kashanian, Amir Ashkan; Kaukab, Fauzia; Koima, Amos Kimutai (Asosiasi Asesmen Pendidikan (AAP), 2026)
Body shaming is a prevalent issue among adolescents and is associated with negative psychological outcomes. This study aimed to examine the predictive effect of body shaming on self-blaming among vocational high school students. A quantitative predictive correlational design was employed, involving 820 students. Data were analyzed using simple linear regression. The results showed that body shaming significantly predicted self-blaming (β = 0.146, p = 0.039). The correlation coefficient (R = 0.346) indicated a weak to moderate relationship, while the coefficient of determination (R² = 0.321) revealed that body shaming accounted for 32.1% of the variance in self-blaming. These findings contribute to the literature by highlighting the role of body shaming in shaping maladaptive self-evaluative processes. Practically, the results emphasize the importance of school-based interventions to reduce body shaming and strengthen adolescents’ self-concept to mitigate negative psychological outcomes.